2016
DOI: 10.1124/jpet.116.236224
|View full text |Cite
|
Sign up to set email alerts
|

Bruton’s Tyrosine Kinase Small Molecule Inhibitors Induce a Distinct Pancreatic Toxicity in Rats

Abstract: Bruton's tyrosine kinase (BTK) is a member of the Tec family of cytoplasmic tyrosine kinases involved in B-cell and myeloid cell signaling. Small molecule inhibitors of BTK are being investigated for treatment of several hematologic cancers and autoimmune diseases. GDC-0853 ((S)-2-(3'-(hydroxymethyl)-1-methyl-5-((5-(2-methyl-4-(oxetan-3-yl)piperazin-1-yl)pyridin-2-yl)amino)-6-oxo-1,6-dihydro-[3,4'-bipyridin]-2'-yl)-7,7-dimethyl-3,4,7,8-tetrahydro-2H-cyclopenta[4,5]pyrrolo[1,2-a]pyrazin-1(6H)-one) is a selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…The lack of a functional effect may correlate to the observations that, even in the more severely affected animals, there are a proportion of islets that are not affected and there may be adequate islet cell reserve capacity. These findings are consistent with Erickson et al’s observation that mild glucose dysregulation levels observed after treatment with GDC-0853 at 100 mg/kg/day for 28 consecutive days did not correlate to the pancreatic changes noted (Erickson et al 2017).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The lack of a functional effect may correlate to the observations that, even in the more severely affected animals, there are a proportion of islets that are not affected and there may be adequate islet cell reserve capacity. These findings are consistent with Erickson et al’s observation that mild glucose dysregulation levels observed after treatment with GDC-0853 at 100 mg/kg/day for 28 consecutive days did not correlate to the pancreatic changes noted (Erickson et al 2017).…”
Section: Discussionsupporting
confidence: 92%
“…The current study is not the first to suggest that susceptibility to the pancreatic effects of a BTK inhibitor varies by rat strain. A recent report investigating the pancreatic effect of other small-molecule BTKi showed that that Crl:CD(SD) rats were the most susceptible to this pancreatic effect, F344 Fischer rats had intermediate (but minimal) susceptibility and Crl:WI(Han) rats had the lowest susceptibility that appeared only with longer treatment (Erickson et al 2017). Based on the data presented in this article and in Erickson et al, the susceptibility of rat strains to these pancreatic effects would be ranked as follows: Crl:CD(SD) > F344 Fischer > Crl:WI(Han) > Hsd: SD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BTK is a proximal kinase in B-cell receptor (BCR) signaling that amplifies activation of several down-stream factors, including PLCg2, ERK, and NFκB, which contribute to both proliferation and survival [ 13 15 ]. BTK is also involved in integrin-mediated adhesion and migration of tumor cells, and contributes to TLR9 signaling via an adaptor function of MYD88 as well [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In animals on maintenance treatment with these specific Syk inhibitors, glucose metabolism starts to deteriorate after only 14 days [42]. The sensitivity of rats to Syk and Bruton's tyrosine kinase inhibitors seems to be strain dependent and to correlate with the background rate of spontaneous hemorrhagic islets [41,43].…”
Section: The Vascular Bed Of the Islets As A Hereto-neglected "Locus mentioning
confidence: 99%